An Administrative Perspective on Psychological Services in Rural School Settings - James McLeskey; Jack A. Cummings; E. Scott Huebner; Nancy L. Waldron (Journal of Research in Rural Education, 1983)
School psychologists practicing in rural settings are faced with unique problems which impede efficient. effective service delivery. These problems relate to traversing geographic distances and hazardous terrain often found in rural areas; overcoming social and cultural barriers; and problems related to the psychologist's professional role. Procedures utilized in addressing these problems are greatly influenced by the psychologist's administrative supervisor. This investigation was undertaken to determine the perspective taken by this administrator regarding these problems in the state of Indiana. The results indicate that heavy caseload and limited special education service delivery options are viewed as the most critical problems. Procedures which may be utilized to circumvent or overcome these problems are discussed.